Arthur Rothstein papers - Rothstein, Arthur, 1915-1985
Correspondence, memoranda, speeches and lectures, writings, notes, subject files, transcripts, press clippings, and other papers relating to Rothstein's career as a photographer for the U.S. Farm Security Administration (FSA) and Look and Parade magazines and as an educator on the subject of photography. Subjects include rural and small town America from 1935 until the early 1940s. Includes a transcript of a 1952 conversation between Roy Emerson Stryker and FSA photographers Dorothea Lange, Rothstein, and John Vachon pertaining to their work.
Library of Congress Prints and Photographs Division.
Photographer. Died 1985.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lange, Dorothea; Stryker, Roy Emerson, -- 1893-1975.; Vachon, John, -- 1914-1975.; United States. -- Farm Security Administration; Look; Parade; Cities and towns -- United States; Country life -- United States; Documentary photography -- United States; New Deal, 1933-1939.; Photography; Photojournalism -- United States; Photographers